Association between baseline tumour burden and outcome in patients with cancer treated with next-generation immunoncology agents. (November 2020) - Tarantino, Paolo; Marra, Antonio; Gandini, Sara; Minotti, Marta; Pricolo, Paola; Signorelli, Giulia; Criscitiello, Carmen; Locatelli, Marzia; Belli, Carmen; Bellomi, Massimo; Curigliano, Giuseppe
Abstract: Background: Baseline tumour burden is a prognostic factor for patients with melanoma and non–small-cell lung cancer treated with immunotherapy. However, no data are available on its role in other solid tumours, nor for treatment with next-generation immunoncology agents (NGIOs). Methods: We reviewed data of patients with any solid tumour consecutively treated at our institution from August 2014 to March 2019, who received ≥1 dose of immune checkpoint inhibitor and/or NGIO within phase 1 trials. Baseline tumour burden was calculated as ∑i Response Evaluation Criteria in Solid Tumours 1.1 baseline target lesions (baseline tumour size [BTS]) or as sum of all measurable baseline lesions (total tumour burden [TTB]); the impact of both parameters on treatment outcomes was investigated. Results: One hundred fifty patients were included in the analysis. Median BTS and TTB were 79 mm and 212 mm, respectively. Objective response rate was found significantly associated with BTS (p < 0.001) and TTB quartiles (p = 0.006), with response rates progressively increasing with decreasing tumour burden quartiles. Both progression-free survival (PFS) (p = 0.001) and overall survival (OS) (p < 0.001) were significantly associated with BTS quartiles, with 26% of the patients progression-free and 56% alive at 12 months in the lower BTS quartile, compared with 3% and 24%, respectively, in the upper quartile. TTB was also significantly associated with OS (P = 0.01) and borderline-significant for PFS (p = 0.07). Multivariate analysis confirmed that baseline burden, also considered as continuous variable, is independently associated with PFS and OS, when assessed with BTS (p = 0.001 and p < 0.001) and TTB (p = 0.007 and p < 0.001). Conclusions: Lower baseline tumour burden is associated with better outcomes in patients with cancer treated with novel immunotherapies. Highlights: Novel immunotherapies beyond anti-PD(L)1 antibodies are under development. Many immunotherapies achieve low response rates in phase 1 trials. Low baseline tumour burden is associated with better outcomes in phase 1 trials. Baseline tumour burden identify patients responsive to novel immunotherapies.